Sistem Perencanaan Manajemen Pendidikan di Madrasah Ibtidaiyah Negeri 2 (MIN 2) Pekanbaru - Deprizon, Deprizon; Fithri, Radhiyatul; Wismanto, Wismanto; Baidarus, Baidarus; Refika, Refika (Program Studi PGMI STAI Auliaurrasyidin Tembilahan, 2023)
Abstract This study describes the education management planning system at Madrasah Ibtidaiyah Negeri 2 (MIN 2) Pekanbaru for teachers in the field of Islamic religious education and class teachers, because the education management planning system is something that is very urgent to be implemented in educational institutions with the aim of improving the quality of education, especially in the field teaching. This research method is Empirical Qualitative by using observation instruments, interviews and documentation, so that the research results illustrate that 78% understand the implementation of the education management planning system at Madrasah Ibtidaiyah Negeri 2 (MIN 2) Pekanbaru.